PEMBERIAN RESTITUSI TERHADAP ANAK SEBAGAI KORBAN KEKERASAN SEKSUAL - Alhabsy, Vedy Riza (Academos, 2023)
Granting of restitution to children is part of the responsibility of the perpetrator based on a court decision that has legal force. This has the aim of protecting children’s rights to live, grow, develop and participate optimally in society without any psychological pressure. The existence of children’s rights as victim of sexual violence has not been fully fulfilled, because in reality restitution is often not carried out properly. This is caused by several factors, such as the lack of awareness of the perpetrators of their responsibilities, the difficulty in obtaining sufficient evidence or information, and the lack of supervision and law enforcement regarding the implementation of restitution. This study aimed whether children as the victim of sexual violence have the right to receive restitution, and how are efforts to provide restitution for children as victims of sexual violence cases. This study used normative legal research with a statutory approach. The results of this study were first, children as victim of sexual violence have the right to receive restitution in Article 71D of Law9number 35 of 2014 concerning4amendments to6Law number 23 of 2002 concerning Children Protection, jo article 7A in Law number 31 of 2014 concerning amendments to Law number 13 of 2006 concerning1Protection of Witnesses and Victims. Second, what are the efforts to provide restitution for children as victim of sexual violence cases Article 7A paragraph (1) Law Number 31 of 2014 concerning the Protection of Witnesses and Victims that every victim has the right to obtain restitution, Government Regulation Number 43 of 2017 regarding the implementation of restitution for children as victim, namely regarding the Rights of Children as victim in prosecution.